Determination of Genetic Relationships among Phalaenopsis Spp. Using Random Amplified Polymorphic DNA and In Vitro Propagation of Phalaenopsis Gigantea - Niknejad, Azadeh (2009)
Phalaenopsis, with long arching sprays of flowers, is among the most beautiful flowers in the world. Phalaenopsis is an important genus and one of the most popular epiphytic monopodial orchids, grown commercially for production of cut flowers and potted plants. Most of them have different and interesting morphological characteristics which have different value to the breeders. Study was carried out using molecular characterization through Random Amplified Polymorphic DNA (RAPD) analyses for 20 species of Phalaenopsis was conducted to determine their genetic variation and relationships. Among the 20 primers used for these analyses, 10 showed polymorphism, with 26 to 54 DNA fragments amplified per primer. A total of 414 polymorphic fragments were generated by these 10 primers and then they were used for correlation grouping analysis. The highest value of Similarity index was 0.28 between Phalaenopsis violacea malaysia and Phalaenopsis violacea witte. The dendrogram resulting from UPGMA hierarchical cluster analysis separated the species into three groups: the first group consisted of five species of Ph. violacea blue, Ph. belina, Ph. violacea malaysia, Ph. violacea witte, and Ph. gigantea; the second group included Ph. lamelligera, Ph. amabilis, Ph. parishii, Ph. labbi nepal, Ph. speciosa, Ph. lobbi yellow, Ph. venosa, Ph. hieroglyphica, and Ph. maculata; the third group consist of Ph. Minho Princess, Ph. Leopard prince, Ph. mannii, Ph. modesta, Ph. cornucervi and Ph. pantherina. RAPD markers can thus be successfully applied to this economically important group of orchids to determine relationship between species of these orchids. Phalaenopsis gigantea one of the most difficult to grow and has the potential of producing beautiful hybrids was selected for further study in developing a rapid and efficient in vitro propagation technique, this technique can also be tested for other species in the future. Ripe capsules of Phalaenopsis gigantea were collected and sterilized. Seed germination was conducted using Vacin and Went (VW) medium supplemented with coconut water (CW) and 6-benzylaminopurine (BAP) and kinetin (KIN). Protocorm-like bodies (PLBs) were successfully induced and plantlets were produced after 60 days. BAP at 1 mgL-1 in combination with 2 mgL-1 KIN produced the highest number of plantlets followed by treatment 1 mgL-1 BAP and 1 mgL-1 KIN. Protocorm-like bodies (PLBs) were successfully induced from leaf segments using New Dogashima medium (NDM) with BAP, Thidiazuron (TDZ), and KIN, each at 0.01, 0.1, 0.5 and 1.0 mg/L alone and in combination with naphthalene acetic acid (NAA), at 0.01, 0.1, 0.5 and 1.0 mgL-1, within 6-8 weeks of culture. The highest percentage of callus formation (100%) was obtained from treatment containing 1 mgL-1 NAA in combination with 0.1 mgL-1 TDZ followed by treatment supplemented with 1 mgL-1 NAA and 0.5 mgL-1 TDZ (76.56%).Plant regeneration from PLBs was achieved in PGR-free NDM basal medium. There was no PLB observed on full and half-strength MS media supplemented with different concentrations of 2, 4-D, BAP and TDZ. Similarly, no PLB was observed on VW and ½ MS media supplemented with different concentrations and combinations with 2, 4.-D, BAP, TDZ and CW or NAA. No PLB was also observed on NDM medium with different concentrations and combinations with BAP and NAA. However multiplication of PLB was observed in liquid media of basal MS, VW, and NDM with or without sucrose. The highest fresh weight of PLBs was obtained from VW medium supplemented with CW.